Thrombotic and Thromboembolic Complications in Patients with Adult Congenital Heart Disease - Bikdeli, Behnood; Green, Phillip; Lewis, Matthew J.; Rosenbaum, Marlon S. (International Journal of Cardiovascular Practice, 2017)
Improved medical and surgical interventions have increased the longevity of patients with congenital heart defects and most such patients live into adulthood. Thrombotic and thromboembolic complications constitute a major cause of mortality and morbidity in patients with adult congenital heart disease (ACHD). Such events include acute coronary syndromes, ischemic stroke (cardioembolic due to thrombus formation in the systemic ventricle, secondary to atrial arrhythmias, or due to paradoxical embolism), and venous thromboembolism. Some thrombotic phenomena are also specific to patients with ACHD, such as those related to Fontan circulation. We provide a succinct overview of thrombotic and thromboembolic complications in patients with ACHD, focusing on stroke and venous thromboembolic events.